1995
DOI: 10.1128/jvi.69.2.748-755.1995
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modifications in cis elements of the long terminal repeat of retroviral vectors lead to increased expression and decreased DNA methylation in embryonic carcinoma cells

Abstract: Infection by murine retroviruses in embryonic carcinoma (EC) and embryonic stem cells is highly restricted. The transcriptional unit of the Moloney murine leukemic virus (MoMuLV) long terminal repeat (LTR) is inactive in EC and embryonic stem cells in association with increased proviral methylation. In this study, expression in F9 EC cells was achieved from novel retroviral vectors containing three modifications in the MoMuLV-based retroviral vector: presence of the myeloproliferative sarcoma virus LTR, substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(65 citation statements)
references
References 44 publications
(55 reference statements)
3
60
0
2
Order By: Relevance
“…The MND-GFP-SN vector, which expresses the GFP from the modified MND long-terminal repeat (LTR) and contains a simian virus-40 neo R cassette, was a kind gift of Dr. D. Kohn (Children's Hospital of Los Angeles, Los Angeles, CA) ( Fig. 1A) [13]. The oncoretroviral vector expressing the B-domain deleted FVIII cDNA from the murine leukemia virus (MLV) LTR was described previously [14].…”
Section: Viral Vector Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MND-GFP-SN vector, which expresses the GFP from the modified MND long-terminal repeat (LTR) and contains a simian virus-40 neo R cassette, was a kind gift of Dr. D. Kohn (Children's Hospital of Los Angeles, Los Angeles, CA) ( Fig. 1A) [13]. The oncoretroviral vector expressing the B-domain deleted FVIII cDNA from the murine leukemia virus (MLV) LTR was described previously [14].…”
Section: Viral Vector Productionmentioning
confidence: 99%
“…In a separate experiment, an oncoretroviral vector was used (MND-GFP-SN), which expressed GFP from a modified LTR that confers long-term expression in various stem cells (Fig. 1A) [13]. Confocal microscopical analysis and flow cytometry indicated that transduction of the human BM mesenchymal cells was significantly more efficient with the lentiviral HIV SIN -CMV-GFP vector (Fig.…”
Section: Gfp Expression In Transduced Bm Mesenchymal Cellsmentioning
confidence: 99%
“…Because RV promoter/enhancers included in LV vectors promote high constitutive transgene expression, two clinical trials for adrenoleukodystrophy have included a RV promoter/enhancer similar to MSCV, termed MND, in the LV to drive high expression of the transgene 4,5,45,46 . In contrast to the vector utilized in ZL34, the adrenoleukodystrophy trial LV placed the RV promoter/enhancer internally, instead of within the LV LTR 4,5,45,46 . Tumor-prone mouse models have suggested that an internal strong promoter/enhancer is less genotoxic than the same promoter/enhancer placed within the LV LTR 39 .…”
Section: Discussionmentioning
confidence: 99%
“…These vectors were based on a modified MLV vector backbone that we developed, named MND. 12 The MND vector, like the MSCV vector, has modifications in the cis-acting transcriptional elements that lead to expression in a higher percentage of hematopoietic and lymphoid cells, at higher levels and with greater persistence over time, compared to the standard MLV vectors. [13][14][15] Additionally, we have included the Woodchuck Hepatitis Virus posttranscriptional regulatory element (WPRE) in some vectors, because of its ability to increase the levels of vector-derived transcripts, which leads to improved titers and gene expression.…”
Section: Evaluation Of New Retroviral Vectors Carrying Anti-hiv-1 Genesmentioning
confidence: 99%